Islamic Monumental Works is important for politic and educational psychology: Key Issues and Recent developments in Indonesia - Asrianti Asrianti; Isnaeni Binti Baas; Elihami Elihami; Yusfika Yusfika (EduPsyCouns: Journal of Education, Psychology and Counseling, 2021)
The aim of this article is to look into the introduction of disaster risk reduction education for Islamic Monumental Works is important for politic and educational psychology. Based on many studies that found promising results, curriculum programs relating to this topic have been marketed over the last decade as capable of reducing catastrophe casualties and increasing resilience. As a result, it is important to assess and overcome any possible obstacles to their progress of key issues and recent developments in Indonesia. The case study in South Sulawesi, a rapidly growing megacity vulnerable to disasters and natural hazards, is included in the paper. Based on previous research, a new approach to assessing the implementation of education programs related to these subjects was created. This research captured children's, school personnel's, and non-governmental organizations' views on the complexities of scaling up disaster risk reduction education in classrooms. The report identified seven main topics and makes some policy proposals for the future. These key issues may also be apparent in many other developing and developed countries, and the proposed suggestions may well be applicable outside Indonesia